2023
DOI: 10.1002/ctm2.1309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IKZF1 genetic mutations as new molecular subtypes in acute myeloid leukaemia

Abstract: Genetic mutations of IKZF1 bared unfavourable prognostic significance in the leukaemogenesis of AML, especially for the hotspot IKZF1 (p.N159S) point mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In our large cohort of 1606 adult AML patients, we found heterozygous SNVs to be the most common mode of alteration while we observed only four frame-shift mutations and only one small deletion of IKZF1 . In accordance with previous results [ 37 , 39 ], we also identified a mutational hotspot in the second N-terminal zinc finger domain at p.N159S, which was present in 19 cases (42.2%). Furthermore, in our cohort alterations were restricted to exons 5–8 while no alterations were detected in exons 1–3.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our large cohort of 1606 adult AML patients, we found heterozygous SNVs to be the most common mode of alteration while we observed only four frame-shift mutations and only one small deletion of IKZF1 . In accordance with previous results [ 37 , 39 ], we also identified a mutational hotspot in the second N-terminal zinc finger domain at p.N159S, which was present in 19 cases (42.2%). Furthermore, in our cohort alterations were restricted to exons 5–8 while no alterations were detected in exons 1–3.…”
Section: Discussionsupporting
confidence: 92%
“…While the authors describe a significantly reduced CR rate for patients with IKZF1 mutations, they did not find a difference in RFS or OS in their overall cohort, however, for patients with high mutational burden of IKZF1 (VAF > 0.2), OS was significantly reduced [ 38 ]. Wang et al [ 39 ] found 23 (4.8%) of 475 AML patients to bear mutated IKZF1 . In RNA sequencing, they delineated three clusters of IKFZ -mutated patients: N159S (40%), co-occurring CEBPA mutations (43%), and others (17%) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang Y et al. found that 23 out of 475 (4.8%) AML patients bear mutated IKZF1 , and delineated three clusters of IKZF -mutated as: N159S (40%), co-occurring CEBPA mutations (43%), and others (17%) ( 102 ). Jäger et al.…”
Section: Roles Of Ikzf1 Mutations In Leukemiamentioning
confidence: 99%